RI 7081 Liquidus Temperatures Of Titaniferous Slags (In Three Parts) 1. TiO2-Al2O3-SiO2-CaO-MgO - Wesley T. Holmes (The National Institute for Occupational Safety and Health (NIOSH), 1968)
This report describes the first phase of an investigation aimed at obtaining a wider knowledge of the problems involved in smelting titaniferous magnetites. Liquidus temperature measurements were made on selected slag compositions in the titania-alumina-silica-calcia-magnesia system. Both the melting-holding-quenching method and the hot-stage microscope method were used in the tests. Liquidus temperatures of slags studied ranged from 1,217° to 1,667° C. The lowest liquidus temperature of the slags occurred when the difference between CaO plus MgO and Si02 was less than 12 weight-percent. Liquidus temperatures were also lowered when Si02 was substituted for Ti02 plus Al2O3 when CaO and MgO levels were held constant. Improved methods for the measurement of liquidus temperatures on very small samples are described.